CHIROPRACTIC CARE FOR THE ORAL HEALTH PROFESSIONAL (International Journal of Ayurveda and Pharma Research, 2019)
The major disability among the various professionals worldwide is musculoskeletal disorders. They impose a burden to the community in both direct costs to health care and indirect costs through reduced work efficiency and productivity. In India, according to epidemiological studies, the community based prevalence of musculoskeletal disorders is about 20% and occupation specific prevalence is as high as 90%. Among the victims, the prevalence of musculoskeletal disorders among Dental surgeons is about 64%, out of which 80% had low back pain at some point of time in their life. Despite the burden, musculoskeletal disorders have not been considered in National health programmes. Bearing in mind musculoskeletal disorder as a public health burden, engaging Chiropractic- a complementary type of medicine in screening and as a part of primary prevention will be a great effort in reducing the future burden to the community.